Post-collisional potassic-ultrapotassic magmatism of the variscan orogen: Implications for mantle metasomatism during continental subduction - Soder, Christian; Romer, Rolf L. (Journal of petrology, 2018)
Mantle-derived potassic to ultrapotassic magmatism is a typical feature of collisional orogens. Potassium-rich magmas recurrently formed across the European Variscides during a period of 50 Myr, following the peak of the orogeny at 340 Ma. Lamprophyre dykes are part of this magmatism and have crust-like trace element patterns, as well as elevated initial 87Sr/86Sr and 207Pb/204Pb and low 143Nd/144Nd along with high mantle-compatible trace element concentrations. This hybrid nature requires at least two source components: subducted continental crustal material and mantle peridotite. Sampling of dyke rocks across tectonic zones of contrasting development reveals two groups of K-rich mantle-derived rocks with distinct trace element patterns and isotopic compositions. The dataset covers a wide range of magma compositions, reflecting their multi-stage petrogenesis. Many of the geochemical characteristics of ultrapotassic magmas, such as very high K2O/Na2O, are already features of the high-pressure crustal melts. Whether the trace element signature is transferred unchanged into these liquids or not largely depends on the behaviour of accessory phases. For instance, high Th/La is related to residual allanite during partial melting of subducted felsic crust. The silica-rich liquids migrate from the slab into the overlying lithospheric mantle. Reaction with peridotitic wall-rocks during channelized flow crystallizes orthopyroxene ± garnet at the expense of olivine, resulting in depletion in Al2O3 and garnet-compatible trace elements in the coexisting melt. Progressive wall-rock interaction causes enrichment in incompatible trace elements and may produce peralkaline melt compositions. These metasomatic agents eventually freeze in the lithospheric mantle, forming non-peridotitic lithologies rich in hydrous minerals such as phlogopite. Variable degrees of melting during post-collisional and later lithospheric extension preferentially affect the heterogeneously metasomatized mantle domains, which results in a broad range of lamprophyre compositions, including amphibole lamprophyres, mica lamprophyres and peralkaline lamproites.